Reflective inquiry in teacher education: interanimating authoritative and internally persuasive discourses. Issue 5 (3rd September 2021) - Vujaklija, Amy
ABSTRACT: Teachers often find themselves in the midst of developing their own ideologies while facing authoritative demands on classroom instruction. Internally persuasive discourses shaping these ideologies come from education theories, methods instruction, professional workshops, and teachers' own research. This narrative inquiry follows four graduate students and the teacher researcher in a graduate education course as they discover ways to improve their classroom practices while finding authoritative voices for themselves. Narrated by the teacher researcher, participants' stories illustrate authoritative discourses in teaching contexts, internally persuasive discourses framing ideologies about teaching, and the reflective inquiry interanimating the two. Using reflective inquiry to mediate authoritative and internally persuasive discourses, participants navigated tensions caused by these two conflicting discourses while experiencing ideological becoming. Findings indicate that multimodal/multigenre inquiry projects provided access, legitimacy, competence, and values. Further, next steps suggest the importance of using reflective inquiry to mitigate contentious discourses in education.